EKSPERIMENTASI MODEL NUMBERED HEADS TOGETHER DENGAN MAKE A MATCH (NHT MM) DAN NUMBERED HEADS TOGETHER DENGAN BAMBOO DANCING (NHT BD) DITINJAU DARI KECERDASAN INTERPERSONAL - Dewi, Arianti Puspita; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this research were to determine: (1) which students mathematics achievement would be better, studentÂ given NHT MM, NHT BD, or direct learning model, (2) which students mathematics achievement would be better, student with interpersonal intelligence of high, medium or low, (3) which students mathematics achievement would be better, student with interpersonal intelligence of high, medium, or low on each learning model, (4) which student mathematics achievement would be better, student given NHT MM, NHT BD, or direct learning model in each interpersonal intelligence. The instruments were used mathematics achievement test and questionnaire of studentâs interpersonal intelligence. The data was analyzed using two ANOVA ways then followed by multiple comparisson tests with using Scheffeâ method. Concluded that: (1) NHT MM model has better mathematics achievement than NHT BD model and direct learning model, while NHT BD model has better mathematics achievement than direct learning model, (2) the students with high interpersonal intelligence has better mathematics achievement than the medium and low interpersonal intelligence students, while the student with medium interpersonal intelligence has better mathematics achievement than the low interpersonal intelligence students, (3) for NHT MM, mathematics achievement of students with high interpersonal intelligence was as good as medium and low interpersonal intelligence, however the mathematics achievement of the students with high interpersonal intelligence were better than the students with low interpersonal intelligence; for NHTBD, the mathematics achievement of students with high intelligence were better than medium and low intelligence, and the mathematics achievement of students with medium intelligence was good as low intelligence; for direct learning, the mathematics achievement of students with high intelligence was better than medium and low intelligence, and the mathematics achievement of students with medium intelligence was good as low intelligence, (4) the students with high, medium, and low interpersonal intelligence have the same achievement of mathematics for the models of NHTMM, NHTBD, and direct learning; for medium and low interpersonal intelligence, the students mathematics achievement treated by NHTMM was better than students treated by NHTBD and direct learning model.Keywords: Numbered Heads Together, Make a Match, Bamboo Dancing, interpersonal intelligence, mathematics achievement.